(untitled) (Proceedings OPTIMAL, 2025)
Non-communicable diseases (NCDs) are one of the leading causes of death and illness in Indonesia, with a prevalence trend that continues to increase every year. This research aimed to describe the characteristics and prevalence of NCDs in the working area of the Integrated Development Post (Posbindu) Kemuning, Pusdikarhanud. This research used a descriptive design with a quantitative approach involving secondary data from health screening activities at Posbindu. Collected data included blood pressure, blood sugar levels, body mass index (BMI), uric acid, and cholesterol levels. The results showed that hypertension and diabetes mellitus were the most dominant types of NCDs, with higher prevalence among individuals over the age of 40. These findings emphasized the importance of Posbindu’s role in early detection and public education to support prevention and control efforts for NCDs. Continuous interventions such as health counselling, routine monitoring, and healthy lifestyle promotion were needed to reduce the incidence of NCDs in the community